PENGARUH GENDER, LOVE OF MONEY, DAN TINGKAT PENDIDIKAN TERHADAP PERSEPSI ETIKA PENGGELAPAN PAJAK : (Studi Pada Karyawan PT. Perkebunan Nusantara 1 Regional VII Unit Beringin, Kabupaten Muara Enim, Provinsi Sumatera Selatan) - Pratiwi, Wegy Aprilia; Suhendar, Suhendar; Verawati, Heni (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to investigate the influence of gender, financial desires, and educational attainment on ethical judgments about tax evasion. Tax evasion remains prevalent in Indonesia, complicating the implementation of professional ethics and tax compliance. According to TPB, attitudes, subjective standards, and attitudinal control, all of which are shaped by internal and external factors, including education and personal values, influence a person’s ethical beliefs.Methods: A total of 83 respondents, selected through simple random sampling, were administered a questionnaire as part of a quantitative research study. Multiple linear regression was used to analyse the data in IBM SPSS Statistics 22.Results: The research findings show that the gender factor has a significance value of 0.015 and a coefficient value of -0.249. This finding indicates that ethical beliefs about tax avoidance are significantly negatively influenced by gender, suggesting that men and women have different ethical perspectives. With a coefficient of -0.383 and a significance of 0.000, the desire for money has a significant detrimental effect on moral reasoning regarding tax avoidance. This indicates that those who are more focused on money are more tolerant of tax avoidance. However, with a coefficient value of 0.060 and a significance value of 0.553, the level of learning has no discernible effect on moral beliefs about tax avoidance. This indicates that a person’s feelings about unethical behavior increase with their level of knowledge.Conclusion and suggestion: The results of this study reinforce the TPB, which explains how behaviour increases with subjective norms, and attitudinal control influences an individual’s ethical judgments about a particular action. Our results strongly suggest that government agencies, tax authorities, and educational institutions are crucial in enhancing tax ethics outreach programs, integrating integrity principles into curricula, and strengthening moral development tactics to prevent future tax fraud. Keywords: Gender, Level of Education, Love of Money, Perception of Tax Evasion Ethics